An Analytical Study of the Assignment (Recitation) Method in Teaching Arabic for Students - Ayu, Citra Sukma; Rahmaini, Rahmaini (Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to analyze the implementation of the assignment (recitation) method in Arabic language learning in Grade VII at MTs Al-Ikhlasiyah Sei Buluh, Serdang Bedagai. Amid the rapid development of digital technology, this school continues to maintain a conventional learning approach. The research employs a descriptive qualitative approach, specifically a field study method. The respondents in this study are 30 students from Grade VII of MTs Al-Ikhlasiyah Sei Buluh. Data collection techniques include observation, interviews, and documentation. The data analysis techniques involve data collection, data reduction, data presentation, and drawing conclusions. To test the credibility of the findings, triangulation was used through various data collection methods. The research subjects are focused on individuals involved in implementing the assignment method, namely the Arabic language teacher of Grade VII and the Grade VII students of MTs Al-Ikhlasiyah Sei Buluh. The results of this study indicate that the analysis of the assignment method (resitation method) in Arabic language learning at MTs Al-Ikhlasiyah Sei Buluh was carried out in accordance with the steps of implementing the resitation method. The teacher first provides an explanation of the educational material, after which students are given tasks to complete. The results of these tasks are then presented in written form, reviewed, and evaluated.